CLINICAL EFFECTIVENESS OF COMPLEX REHABILITATION PROGRAMS FOR PATIENTS WITH DEGENERATIVE-DYSTROPHIC LESIONS OF THE LUMBAR SPINE (Physical Culture and Sport: Scientific Perspective, 2025)
Degenerative changes in the lumbar spine are a common reason for rehabilitation interventions. Rehabilitation is an important part of a conservative treatment program for nonspecific back pain. Due to its analgesic effect, it reduces the number of medications, improves functional capacity, and is aimed at preventing relapses. The aim of the study was to evaluate the effectiveness of rehabilitation methods used in patients with degenerative changes in the lumbar spine. The study was conducted in two groups of patients. In the first group, hardware physiotherapy, physical therapy, and water exercises were used, and in the second group, hardware physiotherapy, physical therapy, spinal traction, and water exercises were used. The effectiveness of complex therapy was assessed using the Oswestry questionnaire, the VAS scale, and functional tests: the Schober test, the Laseg test, and the Biering-Sorensen test. There was a decrease in pain in both groups (p
Keywords: physical therapy; hardware physiotherapy; degenerative-dystrophic changes; lumbar spine